Rebound effects in residential heating: How much does an extra degree matter? - Cécile Hediger (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
Households reactions to efficiency gains in heating, known as rebound effects, are investigated in this article. First, an increase in temperature for households living in more efficient dwellings is studied (direct rebound). This increased temperature is then converted into energy following the heating degree days method. Second, the energy embodied in the re-spending of efficiency gains savings on other goods and services than heating is assessed (indirect rebound). Overall, about 20% of the potential energy savings are taken back by those households adjustments, with a direct rebound estimated between 4% and 7%, and an indirect rebound of 15%. As only a partial direct rebound was considered, these results represent a lower limit. In addition, we find that low income households increase more their heating usage than affluent households when efficiency improves, indicating that buildings retrofits have the potential to improve the living conditions of the poorest households.
Keywords: D12; D90; Q41; Q47; R22; 330; rebound effects; energy efficiency; energy demand; embodied energy; micro data